2019
DOI: 10.3390/molecules24132423
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Use of Purified Grape Pomace as a Fining Agent on the Volatile Composition of Monastrell Wines

Abstract: (1) Background: The lack of viable alternatives for the industrial exploitation of grape pomace is one of the reasons why it is considered a serious environmental pollutant. However, as a byproduct, it could be used as a fining agent, since previous studies have shown that it is able to eliminate undesirable substances in wine. However, the little information available does not describe its effect on wine aroma. (2) Methods: Purified grape pomace extracts were used for fining a red wine and their effect on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Activated carbon has been found to reduce 4-ethylphenol and 4-ethylguaiacol in red wines, while egg albumin, isinglass, chitosan, and carboxymethylcellulose were suggested as other potential agents [18]. Purified grape pomace has been shown to be more effective than other fining agents at removing 4-methylguaiacol from Monastrell wine [19], albeit the researchers did not investigate wine specifically tainted by smoke. A study of smoke-affected Pinot Noir wine found that activated carbon reduced the concentration of guaiacol, 4-methylguaiacol and cresols, while other treatments, such as isinglass and egg albumin, had no effect [20].…”
Section: Introductionmentioning
confidence: 99%
“…Activated carbon has been found to reduce 4-ethylphenol and 4-ethylguaiacol in red wines, while egg albumin, isinglass, chitosan, and carboxymethylcellulose were suggested as other potential agents [18]. Purified grape pomace has been shown to be more effective than other fining agents at removing 4-methylguaiacol from Monastrell wine [19], albeit the researchers did not investigate wine specifically tainted by smoke. A study of smoke-affected Pinot Noir wine found that activated carbon reduced the concentration of guaiacol, 4-methylguaiacol and cresols, while other treatments, such as isinglass and egg albumin, had no effect [20].…”
Section: Introductionmentioning
confidence: 99%
“…The linalool, β-damascenone, citronellol, and nerolidol found in the wines analyzed are responsible for varietal aromas [ 49 ] and may contribute to improving the perception of the fruity, citrus, and floral aromatic aromas in wines [ 50 ]. Linalool and citronellol have aromas of lavender and green lemon, respectively [ 35 ], while nerolidol imparts aromas that are sweet and fruity [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Anise is a plant native to the Middle East that has been used since ancient Egypt, and its major volatile compound is anethol, which is responsible for aniseed's fragrant characteristics [29,48,49]. Anethol was found in very high concentration in Limnos samples, followed by aniseed Muscat samples from Macedonia, while estragole, menthol, 4-anisaldehyde, p-anisaldehyde diethyl acetal, alpha-himachalene, gamma- o-Cymene [34,40,41], alpha-pinene [42][43][44], beta-myrcene [21], D-limonene [21,45], ylangene [18,29], alpha-cedrene [46] and alpha-terpinene [14,29] were detected mostly in Muscat, Muscat of Alexandria and Merlot wines, grape musts, and spirits, as they are characteristic metabolites of these cultivar grapes; however, in this study, their concentration was found to be over 50-fold higher in some Muscat grape marc spirit samples originated from Macedonia. Caryophyllene has been previously found in Cabernet Sauvignon berries [47], while Garcia-Martin et al [35] found terpenols in orujo samples and Giannetti et al [14] and Lukic et al [19] detected terpenes, such as alpha-terpinene, p-cymene, alpha-cubebene, and alpha-calacorene in several European spirit samples.…”
Section: Identification Of Volatile Metabolites In Analyzed Grape Mar...mentioning
confidence: 99%